Unlocking the Employment Potential in the Middle East and North Africa : Toward a New Social Contract - World Bank (Washington, DC, 2013)
The book focuses on the future prosperity of the Middle East and North Africa (MENA) region, which together with other companion volumes-on trade and investment, governance, and gender-contributes to ongoing debates, and dialogues about development in the region, and the development challenges that would allow it to unlock its rich potential for prosperity. Through an introduction to the labor market outcomes in the post-World War Two period, the book presents a comparative perspective on the evolution of State vs. labor relations in the region, defines the social contract within its characteristics, and the external factors that contribute to it. State regulations and interventions were extensive, and, it is stipulated the economic future of the region will largely be determined by the fate of its labor markets. The book provides a comprehensive account of recent employment outcomes, and, outlines the policy reforms required to improve the performance of the region's labor markets. But the book goes beyond a technical discussion of labor market outcomes, and investigates the broader political-economic aspects of state-society relations. It integrates questions on how to build vibrant labor markets, and restore the region's growth performance, into a framework that also addresses issues of population dynamics, socioeconomic trends, employment regulations, the quality of institutions, opportunities in the world economy, and the impact of a redistributive social contract on prospects of reform.